STRATEGI PERGURUAN TINGGI DALAM UPAYA MENINGKATKAN KUALITAS SUMBERDAYA MANUSIA - Widodo, Wahyu; Maryadi, Maryadi (MAJALAH ILMIAH LONTAR, 2010)
Â The globalication are demans the increasing quality of the human resources so that they are able to play an active and productive role by taking the education in all fields and levels into the first priority. The hight learning institution as on institution which develops vision and mission to promote the human resource has the main role and strategie position. The logical consequence of this is that university must be able to carry out and to complete that vision and mission successfully, so that the quality of the human resources can increase significantly which is in accordance wich the demand development of the era, which can accommodate the kocal initiatives, nasional interest and global funcsion. Â Â Kata â kata kunci : Era global, Partisipasi Pendidikan, Kebijakan, Strategi